Reinforcement and optimization of hydroxyethyl cellulose / poly (vinyl alcohol) with cellulose nanocrystal as a bone tissue engineering scaffold - Nor Sarahtul Nadirah, Hairol Nizan (2021)
Biomaterial is a medical terminology that is used to describe all natural or synthetic resources such as polymer s that are useful in the introduction of living tissue as part of medical devices or implants without causing any adverse immune rejection react ions. Cellulose has been extensively explored over many decades as one of the biomaterials used in tissue engineering applications due to their unique properties which are low cost, good biocompatibility and good mechanical properties. Preparation of cellu lose nanocrystals (CNC) from cellulose pulp is an alternative way to fulfil the demand for CNC. In tissue engineering, replacement or regeneration of damaged bone is a major challenge in orthopaedic surgery. Hence, scaffold-based bone tissue engineering is designed to overcome these bone defects. This report is comprised of two parts. The first part is about the fabrication and characterization of CNC while the second part is the fabrication and characterization of scaffolds including in vitro degradation a nd cell culture studies. In this present work, CNC produced from empty fruit bunch (EFB) was successfully fabricated by acid hydrolysis. Cellulose pulps were heated at 85 °C in 65 % of sulphuric acid. The cellulose suspension was diluted, centrifuged, sonicated, and then freeze-dried to obtain the CNC. The CNC acted as nanofillers in scaffolds and was physically, chemically and thermally characterized by using field emission scanning electron microscope (FESEM), attenuated total reflectance-Fourier transform infrared spectroscopy (ATR-FTIR) and differential scanning calorimetry (DSC). FESEM results showed that CNC appeared in a spherical shape with particle dimensions in the range of 5 to 30 nm in diameter. The absorption spectra of CNC appeared in specific bands which were at 1045, 1346, 1637, 2903, and 3391cm−1. DSC thermograms shows that the melting temperature, Tm was at 336.4 °C, while the glass transition temperature, Tgwas 43.5 °C. Next, a porous three-dimensional (3D) scaffold of HEC/PVA and HEC/PVA/CNC were successfully fabricated by freeze-drying technique. HEC (5 wt%) and PVA (15 wt%) were dissolved and blended at a ratio of 50:50 and incorporated with various concentrations of CNC (1, 3, 5 and 7 wt%). The morphology, mechanical and thermal properties of scaffolds were characterized by SEM, ATR-FTIR, DSC, thermogravimetric analysis (TGA), and universal tensile machine (UTM). The degradation behaviours of scaffolds were characterized by a series of analyses including swelling ratio, weight loss and pH changes. Meanwhile, cytotoxicity studies on both porous scaffold biomaterials were carried out by utilizing human fetal osteoblast (hFOB) cells using MTT assays and cell-scaffold morphological study. HEC/PVA incorporated with CNC exhibited superior functionality which resulted in decreased average pore size and there were some slight changes in the chemical structure as determined by FTIR spectra. Thermal studies revealed that the melting temperatures of HEC/PVA/CNC scaffold were slightly shifted to a higher value. Furthermore, it can be seen that the addition of CNC resulted in increases in the ultimate tensile stress (from 0.18 to 0.92) and ultimate tensile strain (from 5.83 to 11.03). Hence, it offers a very good mechanical performance. The cell culture study revealed that the hFOB cells were able to attach and spread on all scaffolds and supported the cell adhesion and proliferation. The optimum concentration of CNC was at 3 and 5 wt% while further addition of CNC reduced the cell viability. Due to its biocompatible and biodegradable properties, these newly developed highly porous scaffolds may provide a promising alternative scaffolding matrix for bone tissue engineering regeneration.